PERAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL MEDIASI PADA PENGARUH STRES KERJA TERHADAP TURNOVER INTENTION KARYAWAN - Sidi Mantra, Anak Agung Bagus Alit; Rahyuda, Agoes Ganesha (E-Jurnal Manajemen, 2021)
The purpose of this study was to determine the role of organizational commitment as a mediating variable on the effect of job stress on employee turnover intention at PT. BPR Pedungan. This research was conducted on employees of PT. BPR Pedungan, with a sample size determined through a saturated sample technique, as many as 75 employees. Data were analyzed using path analysis techniques. Collecting data through interviews and distributing questionnaires. The results of this study indicate that job stress has a negative and significant effect on organizational commitment. Job stress has a positive and significant effect on turnover intention. Organizational commitment has a negative and significant effect on turnover intention. Organizational commitment positively and significantly mediates the effect of job stress on employee turnover intention at PT. BPR Pedungan. Keywords : job stress, organizational commitment, turnover intention